Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1096/fasebj.21.5.a182-a
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Lamin A/C and their binding partners and nuclear envelope phenotype in cardiomyocytes from Dilated cardiomoyopathy patients

Abstract: Lamin A/C gene is one of most frequently reported mutated genes in dilated cardiomyopathy which is characterized by the dilatation of cardiac chambers and impaired contraction. Lamin A and C are major components of the nuclear lamina. From a cohort of DCM patients, we selected seven patients displaying major cardiomyocytes nucleus envelope abnormalities on electron microscopy images. In the DNA from these patients, we screened both Lamin A/C and thymopoietin genes for mutations by direct sequencing. Thymopoiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Minor nuclear defects are a normal feature of nucleated cells. It has been shown that the amount of dysmorphic nuclei increases with age, 4 and that cardiac cells have more dysmorphic nuclei than skin fibroblasts, 25 which is also confirmed by our data [Fig. 2c(vi)].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Minor nuclear defects are a normal feature of nucleated cells. It has been shown that the amount of dysmorphic nuclei increases with age, 4 and that cardiac cells have more dysmorphic nuclei than skin fibroblasts, 25 which is also confirmed by our data [Fig. 2c(vi)].…”
Section: Discussionsupporting
confidence: 91%
“…2c(vi)]. 4 As expected, 25 for each individual the amount of dysmorphic nuclei was significantly higher in cardiac tissue than in fibroblasts. The increase itself was significantly greater for PA1 [Fig.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation